2017
DOI: 10.3390/ma10080872
|View full text |Cite
|
Sign up to set email alerts
|

Use of Almond Shells and Rice Husk as Fillers of Poly(Methyl Methacrylate) (PMMA) Composites

Abstract: In recent years, wood fibres have often been applied as the reinforcement of thermoplastic materials, such as polypropylene, whereas their use in combination with thermosetting resin has been less widespread. This study concerns the production of PMMA-based composites by partly replacing alumina trihydrate (ATH) with wood waste fillers, namely rice husks and almond shells, which would otherwise be disposed by incineration. The amount of filler introduced was limited to 10% as regards rice husks and 10 or 15% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…Observed areas showing the presence of spherical shapes, determined by the shape of PMMA pre-polymerized particles of the "powder" component, indicated a significant local reduction in material strength as a consequence of filler aggregations, leading to uprooting of these particles from the cured material and probably accelerated fracture of samples. A similar decrease in the mechanical properties along with the increase in mass concentrations of fillers has been noted after the introduction of particles, e.g., ZrO 2 , nanodiamonds, Al 2 O 3 , hydroxyapatite, titanium oxide, ground fillers of natural origin or even glass fibers [83,[87][88][89]. On the other hand, potential reinforcement in many cases can be achieved by using the synergistic effect of various additives (e.g., different particles, glass meshes, and glass fibers) [90].…”
Section: Discussionsupporting
confidence: 57%
“…Observed areas showing the presence of spherical shapes, determined by the shape of PMMA pre-polymerized particles of the "powder" component, indicated a significant local reduction in material strength as a consequence of filler aggregations, leading to uprooting of these particles from the cured material and probably accelerated fracture of samples. A similar decrease in the mechanical properties along with the increase in mass concentrations of fillers has been noted after the introduction of particles, e.g., ZrO 2 , nanodiamonds, Al 2 O 3 , hydroxyapatite, titanium oxide, ground fillers of natural origin or even glass fibers [83,[87][88][89]. On the other hand, potential reinforcement in many cases can be achieved by using the synergistic effect of various additives (e.g., different particles, glass meshes, and glass fibers) [90].…”
Section: Discussionsupporting
confidence: 57%
“…This powerful area of interest presents several benefits such as biodegradability in combination with bio-based or natural polymers, light weight, low cost and easy processing [14,15]. Among the wide variety of lignocellulosic wastes, almond shell powder has been already considered as filler for commodity plastics, such as polypropylene [16][17][18][19][20], polyethylene [21], poly(methyl methacrylate) [22] and toughened epoxies [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The publication [9] reviewed the reinforcement of composites with plant waste, such as rice husks and almond shells. It is shown that the greatest improvement of polymer properties is limited by the filler share of 10-15 %, over which there is a deterioration of the mechanical properties and operational characteristics.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%